Ohmic Heating (OH)-Assisted Extraction of Bovine Hide Gelatin: Functional and Physicochemical Comparison With Halal Commercial Gelatins - Demirel, Fatma Tuba Kirac; Isik, Cigdem Akdemir; Parlak, Mahmut Ekrem; Odabas, Halil Ibrahim; Dagdelen, Adnan Fatih; Saricaoglu, Furkan Turker (Wiley, 2026)
Conventional gelatin extraction from high-collagen tissues requires prolonged thermal processing (8-10 h), resulting in high energy consumption and potential degradation of functional properties. To address this limitation, this study investigated ohmic heating (OH) as an alternative extraction method for bovine hide gelatin. Gelatin was extracted using voltage gradients of 5-20 V/cm for 1-5 h and compared with both conventional extraction parameters and commercial halal gelatins. OH markedly reduced the extraction time to 1-5 h while maintaining a maximum temperature of 70 degrees C, resulting in significantly improved extraction efficiency and higher dry matter and protein contents (p < 0.05). Although gel strength (122.12-176.81 g) was lower than that of commercial bovine gelatin (242.44 g), all OH-treated samples except those extracted at 20 V/cm formed stable gels. SDS-PAGE and compositional analyses indicated that OH induced partial degradation of high-molecular-weight fractions, consistent with the observed gel strength trends. The amino acid profiles, dominated by glycine, proline, and hydroxyproline, and the viscoelastic behavior (G ' > G '') were comparable to commercial references. Thermal analyses further revealed sharper melting transitions and higher Delta H values, suggesting improved thermal stability. Microstructural changes in pore size and distribution supported the observed functional differences. Overall, OH-assisted extraction provides an efficient, energy-saving, and thermally controlled approach to gelatin production. To our knowledge, this is the first study to demonstrate the applicability of ohmic heating for extracting gelatin from bovine hide, underscoring its potential as a sustainable alternative to conventional processing methods.
Keywords: collagen hydrolysis; halal biopolymer; novel heating technologies; protein functionality; sustainable extraction